(untitled) (Comprehensive Journal of Science, 2026)
This experiment was conducted to determine the effect of surgical removal of the oil gland at 10, 15, and 20 days of age on the productive performance of broiler chickens for the following traits: final body weight (42 days), total weight gain, cumulative feed consumption, feed conversion ratio, mortality rate, dressing percentage, recovery rate, productivity per square meter, and production index at the end of the experimental period. One hundred and twenty on day old Ross 308 broiler chickens were used in the study. They were randomly divided into four treatments, with 30 birds per treatment and 10 birds per replicate. The first treatment (T1), the control, was left without the oil gland removal. the oil gland was surgically removed in the second treatment (T2) at 10 days of age, the third treatment (T3) at 15 days of age, and the fourth treatment (T4) at 20 days of age, respectively. The results for the productive traits, including average bird weight at 42 days of age, average cumulative weight gain, feed conversion ratio, production per square meter of chickens, dressing percentage, recovery percentage, and production index, showed a significant advantage for the birds in the treatments (T2) surgical removal of the oil gland at 10 days, (T3) surgical removal of the oil gland at 15 days, and (T4) surgical removal of the oil gland at 15 days, at a level of P<0.05, over the birds in the control treatment (T1) without oil gland removal. Regarding average cumulative feed consumption, no significant differences were found at a level of P<0.05 between the birds in all treatments. As for the mortality rate (%), it was not affected among the birds in any of the treatments. We conclude from this study that surgical removal of the oil gland in broiler chickens at the age of 10 days, 15 days, and 20 days improved production efficiency because it prevented the concentration of the basic raw materials needed by the body inside the oil gland, which worked to return them to the bloodstream and then benefit from them in raising the rate of metabolism and protein synthesis, which contributed to a significant improvement in production performance. This is considered evidence that removal of the oil gland affects metabolic processes that positively affect production efficiency in broiler chickens.